ChemInform Abstract: Three‐Step Synthesis of Fluoranthenes Through Pd‐Catalyzed Inter‐ and Intramolecular C—H Arylation. Issue 37 (August 2016) - Yamaguchi, Miyuki; Higuchi, Mayu; Tazawa, Kanae; Manabe, Kei
Abstract: Starting from α‐naphthols and halobenzenes, a three‐step procedure involving Miura′s intermolecular C—H arylation, O‐derivatization to form a suitable leaving group, and intramolecular C—H arylation leads to a series of fluoranthenes.